2021
DOI: 10.1109/ted.2021.3050432
|View full text |Cite
|
Sign up to set email alerts
|

Application of a Thin-Film Transistor Array for Cellular-Resolution Electrophysiology and Electrochemistry

Abstract: The constant development and improvement of microelectromechanical systems (MEMS) have been given a great opportunity to develop new reliable microsystems devices for biomedical research. This article presents a locally addressable 2-D arrayed indium-tin oxide microelectrode platform with integrated thin-film transistors (TFTs) for biological and chemical sensing. Microelectrode arrays (MEAs) using TFT have the advantage of being transparent with a high density of microelectrodes on a large surface. In vitro 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Finally, the authors demonstrated cyclic voltammetry and amperometry experimental results with the TFT-device, in agreement with results obtained with a standard gold working electrode. Amperometry was performed on Tyramine and the smallest concentration detected was 10μM [7].…”
Section: ) Chemical Sensingmentioning
confidence: 99%
“…Finally, the authors demonstrated cyclic voltammetry and amperometry experimental results with the TFT-device, in agreement with results obtained with a standard gold working electrode. Amperometry was performed on Tyramine and the smallest concentration detected was 10μM [7].…”
Section: ) Chemical Sensingmentioning
confidence: 99%
“…1). Our group has already published results demonstrating measurement of the electrophysiology activity of cardiac muscle cells (cardiomyocyte cell) cultured on a TFT platform, as well as cell culture monitoring using impedance spectroscopy [6,7]. In this article, we present results of electrical stimulation of a cardiomyocyte cell culture with a TFT platform.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the research group of the authors has got interest in using the TFT technology for biological applications, such as electrophysiology, cells culture monitoring by impedance sensing and bio-sensing [3][4][5]. Actually, when compared to commercial MEAs with 64 electrodes per chip in general, TFT-µEAs are advantageous in higher electrode density with about 1.2 × 10 4 electrodes cm -2 (50-100 µm pitches and ∼5 µm spacing between neighboring electrodes) to avoid misaligning with cells, size of which is about 10-20 µm in diameter [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Bakkum et al have conducted a two-dimensional mapping analysis for cell viability and function using human-derived cells, such as human hepatocarcinoma cell line Hep G2, by electrical impedance variation simultaneously with microscopic observation of fluorescent imaging on the transparent TFT-µEAs [2]. Furthermore, real-time extracellular potential measurement for cardiomyocytes and neural cells was also performed with similar devices toward the application to electrophysiological research [4,5]. It offers an alternative to MEA and CMOS for characterizing two-dimensional analyses of cardiomyocytes and neural cells on a large surface, with using high resolution and a dimension of pixels is as small as few cells.…”
Section: Introductionmentioning
confidence: 99%